Factors affecting students' learning from a design‐based implementation research project in diverse education systems. Issue 5 (21st January 2022) - Lin, Qinyun; Frank, Kenneth A.; Bathia, Shruti; Draney, Karen; Thomas, Jay; Anderson, Charles W.
Abstract: This article reports on quantitative findings from a design‐based implementation research (DBIR) project Carbon TIME that focused on teaching carbon cycling at multiple scales, from atomic‐molecular to global. We report results from a large dataset from diverse schools, including 59, 654 student assessments of three‐dimensional learning aligned with Next Generation Science Standards collected in classrooms of 133 middle‐ and high‐school teachers over a 4‐year period. We used a subset of these data to investigate factors related to students' learning in this large and diverse set of classrooms. Our findings included: First, Carbon TIME 's curriculum and professional development were associated with substantial improvements in overall student achievement; within classrooms students with lower pretest scores had higher learning gains. Second, differences among individual teachers accounted for more of the variance in student learning gains than other measures including school demographics and students' prior knowledge. Third, school demographic factors (percent free and reduced lunch and percent marginalized students of color) had statistically significant but small effects on students' learning. Finally, sustained investment and participation were important; student learning gains improved across years for the project as a whole, and for individual teachers as they gained experience and participated in professional development. These findings contribute to programs of systemic changes to support three‐dimensional science learning.